A mathematical model of immunomodulatory treatment in myocardial infarction. (7th July 2022) - Moise, Nicolae; Friedman, Avner
Highlights: The article is the first to describe a spatial mathematical model of myocardial infarction. It is based on a network of complex interactions between inflammatory cells, cytokines and local cardiac myocytes. The model predicts several useful new drug combinations. Abstract: A heart attack, or acute myocardial infarction (MI) is caused by the acute occlusion of a coronary artery. MI is associated with 30% mortality; approximately half of the deaths occur prior to arrival at the hospital. Reperfusion therapy in the hospital is a medical treatment to restore blood flow through the blocked artery; treatment includes drugs and surgery. However, the damage to the heart muscles through the infarct area is permanent and there is additional damage around the infarct area due to inflammation or insufficient oxygen supply. Approximately half of the patients who survive MI are hospitalized again within one year after reperfusion treatment. In this paper we develop a mathematical model of MI and use it to assess the efficacy of drugs used, post reperfusion, to reduce the damage caused by inflammation in a region of the left ventricular wall surrounding the infarct area. The mathematical model, represented by a system of partial differential equations. The model variables include myocytes, endothelial cells, neutrophils, macrophages, fibroblasts and cytokines that play a role in the interactions among these cells. The drugs used to in the model include IL-1, TNF- α and TGF- β inhibitors, and the delivery of VEGF. The model is based on mice data. In particular, we find that immunomodulatory treatment with TNF- α and IL-1 inhibitors can significantly increase the low density of myocytes bordering the infarct area by 50–60% and decrease the abnormally high density of ECM in a region surrounding the infarct area.